1992
DOI: 10.1034/j.1399-3054.1992.850115.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the photosynthetic capacity of primary bean leaves by the red:far-red ratio and photosynthetic photon flux density of incident light

Abstract: 1992. Regulation of the photosynthetic capacity of primary bean leaves by the red:far-red ratio and photosynthetic photon flux density of incident light. -Physioi. Plant. 85: 97-101,The main objective of the present work was to examine the effects of the red:far-red ratio (R:FR) prevailing during leaf development on the photosynthetic capacity of mature leaves. Plants of Phaseotus vulgaris L. cv. Balin de Albenga were grown from time of emergence in a controlled environment room, 25 ± 3*C, 12-h photoperiod, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
3
18
1
2
Order By: Relevance
“…(Light-Emitting Diodes, LEDs) (Barreiro et al, 1992;Hoenecke et al, 1992;Hunter and Burritt, 2004;Heo et al, 2006;Massa et al, 2008;Morrow, 2008;Olle and Viršile, 2013;Chen et al, 2014).…”
Section: Research Articlementioning
confidence: 99%
“…(Light-Emitting Diodes, LEDs) (Barreiro et al, 1992;Hoenecke et al, 1992;Hunter and Burritt, 2004;Heo et al, 2006;Massa et al, 2008;Morrow, 2008;Olle and Viršile, 2013;Chen et al, 2014).…”
Section: Research Articlementioning
confidence: 99%
“…From this study, it was suggested that the leaf growth and secondary metabolism of Kale seedlings can be controlled by supplementary radiation using red LEDs of 1.2 μmol/m 해 태양광 입사량이 부족해지거나 계절적으로 일장이 짧아지 는 시기에는 작물의 광합성과 생장을 촉진시키기 위해서는 인공광을 이용하여 온실내 부족한 광을 인위적으로 보충해주 는 보광기술이 필요하다 (Albright, 1997;Dorais, 2003;Heo et al, 2010;2011a;2011b). 온실재배 작물의 영양생 장 및 생식생장에 영향을 미치는 다양한 환경요인 중에서 광 강도와 광질은 보광을 위해 사용하는 인공광원의 영향을 받 게 되는데, 온실과 같은 시설에서는 주로 고압나트륨등, 삼파 장등, 백열등이나 메탈할라이드등과 같은 광원을 이용하여 보 광하고 있다 (Farina and Veruggio, 1996 (Bula et al, 1991;Barreiro et al, 1992;Tanaka et al, 1998;Heo et al, 2011a;2011b;Chen et al, 2014). LEDs는 다른 인공광원에 비해 전력소 모량이 적고 램프 수명이 길며 광질을 용이하게 제어할 수 있 다는 특징이 있어, 현재 다양한 작물 재배를 위한 인공광원으 로써의 이용성이 검토되고 있다 (Hoenecke et al, 1992;Hunter and Burritt, 2004;Morrow, 2008;Heo et al, 2009;Olle and Akvile, 2013 …”
unclassified
“…From this study, it was suggested that the leaf growth and secondary metabolism of Kale seedlings can be controlled by supplementary radiation using red LEDs of 1.2 μmol/m 해 태양광 입사량이 부족해지거나 계절적으로 일장이 짧아지 는 시기에는 작물의 광합성과 생장을 촉진시키기 위해서는 인공광을 이용하여 온실내 부족한 광을 인위적으로 보충해주 는 보광기술이 필요하다 (Albright, 1997;Dorais, 2003;Heo et al, 2010;2011a;2011b). 온실재배 작물의 영양 생장 및 생식생장에 영향을 미치는 다양한 환경요인 중에서 광강도와 광질은 보광을 위해 사용하는 인공광원의 영향을 받게 되는데, 온실과 같은 시설에서는 주로 고압나트륨등, 삼 파장등, 백열등이나 메탈할라이드등과 같은 광원을 이용하여 보광하고 있다 (Farina and Veruggio, 1996 (Bula et al, 1991;Barreiro et al, 1992;Tanaka et al, 1998;Heo et al, 2011a;2011b;Chen et al, 2014). LEDs는 다른 인공광원에 비해 전력소 모량이 적고 램프 수명이 길며 광질을 용이하게 제어할 수 있 다는 특징이 있어, 현재 다양한 작물 재배를 위한 인공광원으 로써의 이용성이 검토되고 있다 (Hoenecke et al, 1992;Hunter and Burritt, 2004;Morrow, 2008;Heo et al, 2009;Olle and Akvile, 2013 …”
unclassified